2015
DOI: 10.1007/s10803-015-2546-y
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Patterns of Eye Movements in Face to Face Conversation are Associated with Autistic Traits: Evidence from a Student Sample

Abstract: The current study investigated whether the amount of autistic traits shown by an individual is associated with viewing behaviour during a face-to-face interaction. The eye movements of 36 neurotypical university students were recorded using a mobile eye-tracking device. High amounts of autistic traits were neither associated with reduced looking to the social partner overall, nor with reduced looking to the face. However, individuals who were high in autistic traits exhibited reduced visual exploration during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
67
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 53 publications
11
67
4
Order By: Relevance
“… Note the results we report for the mouth control region were replicated for an alternative larger control region comprising the entire bottom half of the face (e.g., as used by Vabalas & Freeth, ; see Supporting information). …”
supporting
confidence: 60%
See 1 more Smart Citation
“… Note the results we report for the mouth control region were replicated for an alternative larger control region comprising the entire bottom half of the face (e.g., as used by Vabalas & Freeth, ; see Supporting information). …”
supporting
confidence: 60%
“…Moreover, a similar contradiction is present even in reviews and meta‐analyses, with a conclusion of reduced looking at eyes in ASD in Papagiannopoulou, Chitty, Hermens, Hickie, and Lagopoulos (), but not in Falck‐Ytter and von Hofsten (), or Guillon, Hadjikhani, Baduel, and Rogé (). Further, the contradiction is also present in the smaller number of studies testing the general population: for example, one study has found higher autistic traits to be associated with less eye contact in response to direct gaze (Chen & Yoon, ), but another found higher autistic traits showed no association with proportion of looking to the eye half of the face (i.e., the top half) compared to the non‐eye half (i.e., the bottom half; Vabalas & Freeth, ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, evidence from studies of individual differences in the general population is not entirely consistent with the evidence provided by Freeth and Bugembe's case-control study. Neither, Vabalas and Freeth (2016), nor Freeth et al (2013), found a significant correlation between the number of autistic traits self-reported by neurotypical adults and the number of looks to the experimenter during a live interaction with a social partner (Freeth, Foulsham, & Kingstone, 2013). On the other hand, Vabalas and Freeth (2016) did find that participants with higher numbers of autistic traits manifested in a reduced tendedency to explore the scene visually.…”
mentioning
confidence: 78%
“…They can have difficulty disengaging from an initial point of fixation (Kikuchi et al 2011;Landry and Bryson 2004) and in demanding tasks tend to display reduced saccadic activity (Kemner et al 1998;Goldberg et al 2002). In line with this Vabalas and Freeth (2015) recently found that during a face-to-face interaction individuals who were high in autistic displayed restricted eye-movements (shorter and less frequent saccades) compared to peers who were low in autistic traits. Visual inspection of objects is also often prolonged or unusual in infants who later develop ASD (Ozonoff et al 2008).…”
Section: Individuals With Asd Generally Display Heightened Attention mentioning
confidence: 94%